Negative word of mouth on social media: A case study of Deutsche Bahn's accountability management - Milad Mirbabaie; Stefan Stieglitz; Julian Marx (Schmalenbach Journal of Business Research (SBUR), 2023)
Our study addresses whether a chief executive officer's (CEO) personality can mitigate financial constraints' negative effect on employee satisfaction. We draw on extant research that establishes this negative effect but add an upper echelon's perspective by examining the potential influence of the CEO's personality traits. Using a multi-source dataset of 1516 observations of S&P 500 firms, novel measures of employee satisfaction based on Glassdoor reviews, and a machine-learning-based linguistic tool on the Five-Factor Model's personality traits, our study reveals that a CEO who has a high level of openness to experience and/or a low level of conscientiousness buffers the negative impact of financial constraints on employee satisfaction. Theoretical and practical implications are discussed.
Keywords: M30; O35; 650; Negative Word-of-Mouth; Accountability; Social Media; Twitter